Dismutational and Global‐Minimum Isomers of Heavier 1, 4‐Dimetallatetrasilabenzenes of Group 141. Issue 13 (26th February 2014) - Jana, Anukul; Huch, Volker; Repisky, Michal; Berger, Raphael J. F.; Scheschkewitz, David
Abstract Aromatic species with heavier Group 14 elements show remarkable differences in terms of stability, structure, and reactivity. Herein we report our experimental and theoretical investigations regarding isomers of germanium‐ and tin‐containing benzene analogues E2Si4R6 (E=Ge, Sn). The germanium‐substituted dismutational isomer with a tricyclic six‐membered scaffold is isolable, but unlike the homonuclear Si6 analogue slowly rearranges even at room temperature to give the propellane‐type global minimum isomer. In case of E=Sn the dismutational isomer may be an intermediate on the pathway to the propellane‐type species obtained, but cannot be detected even at low temperature. Unprecedentedly large chemical shift anisotropies in the 29Si NMR spectra that increase from the Si6 species through Ge2Si4 to Sn2Si4 are rationalized by progressively larger paramagnetic‐term contributions to the chemical shift tensor as a result of diminishing HOMO–LUMO gaps, which are also reflected in the absorption spectra, as well as by appearance and symmetry of these frontier orbitals.